Trabalho e Educação: (des) emprego na Bahia - Jorge, Marcos [UNESP]; Campos, Maria de Fatima Sales de Souza; Telles, Tiago Santos (My University, 2010)
The article argues about the problematic of the technological modernization of the productive system, from years 80 and intensified in the 90, and its effect on the behavior of the labor market based in the state of the Bahia. From the few Demographic data of Census 2000 by the IBGE an analysis of the Bahia state force of work was affected mainly on the variable as employment, wage profit, race, sort and years of studies. The data show, among others questions, a labor market with a low-level of education and low wages with strong exclusion in relation to the race and sort.

O artigo discute a problemática da modernização tecnológica do sistema produtivo, a partir dos anos 80 e intensificada na década de 90, e seus efeitos sobre o comportamento do mercado de trabalho, focando o estado da Bahia. A partir dos microdados do Censo Demográfico 2000, do IBGE, efetuou-se uma análise da força de trabalho baiana, destacando variáveis como empregabilidade, ganho salarial, raça, gênero e tempo de estudo. Os dados mostram, entre outras questões, um mercado de trabalho de baixo nível educacional e baixos salários com fortes linhas de exclusão em relação à raça e gênero.
Work and Education: (un)employment in Bahia State, Brazil
Keywords: Labor market; Unemployment; Gender; Race; Mercado de trabalho; Escolaridade; Desemprego; Gênero; Raça